2012
DOI: 10.1186/2049-1891-3-20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex and rearing system on the quality and mineral content of fiber from raeini cashmere goats

Abstract: The aim of this study was to compare the quality characteristics and mineral content of the fiber from male and female cashmere goats raised under different management systems. Male and female Raeini cashmere goats (<1.5 years of age, n = 48) were selected from flocks raised at a government breeding station or raised commercially under either rural or nomadic conditions. The staple length, cashmere fiber diameter, coefficient of variation for fiber diameter, percentage of cashmere in a fleece, percentage of gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…The mean fibre diameter of male and female Liaoning cashmere goats is 16.12 mm and 15.97 mm, respectively (Wu 2018). Shamsaddini-Bafti reported that the mean fibre diameter of Raeini cashmere goats is approximately 18.0 mm (Shamsaddini-Bafti et al 2012). The cashmere production in our study was higher than that found for Long Dong cashmere goats (Xue et al 2011).…”
Section: Discussioncontrasting
confidence: 71%
“…The mean fibre diameter of male and female Liaoning cashmere goats is 16.12 mm and 15.97 mm, respectively (Wu 2018). Shamsaddini-Bafti reported that the mean fibre diameter of Raeini cashmere goats is approximately 18.0 mm (Shamsaddini-Bafti et al 2012). The cashmere production in our study was higher than that found for Long Dong cashmere goats (Xue et al 2011).…”
Section: Discussioncontrasting
confidence: 71%
“…The cashmere obtained from goats ( Capra hircus ), is one of the finest and softest fibres produced by animals and is used exclusively in the production of luxurious textile products [ 1 ]. Cashmere, famous for its high performance and rareness, is more expensive than wool with an identical diameter [ 2 ] and the demand for it is growing [ 3 ]. The majority of cashmere is produced in China, Mongolia, Iran and several other countries, where cashmere production makes an important contribution to the economy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Liaoning Cashmere goat is one of the major Cashmere goat breeds in China, which is famous for its higher cashmere yield, higher net cashmere rates and stable heritability. Unlike wool and mohair, the growth and zinc (Zn) content of cashmere were affected by rearing systems for its seasonal growth (Shamsaddini‐Bafti et al., ). In China, the recommended dietary Zn levels for cashmere goats are based on earlier research on grazing.…”
Section: Introductionmentioning
confidence: 99%